Outpatient Expectant Management of Term Prelabor Rupture of Membranes: A Retrospective Cohort Study - Chacón, Kelly M.; Bryant Mantha, Allison S.; Clapp, Mark A. (American Journal of Perinatology, 2019)
Objective To examine outcomes among women with prelabor rupture of membranes (PROM) who declined induction and chose outpatient expectant management compared with those admitted for induction.Study Design This is a retrospective cohort study of term women with singleton, vertex-presenting fetuses who presented with PROM between July 2016 and June 2017 and were eligible for outpatient expectant management (n = 166). The primary outcomes were time from PROM to delivery and time from admission to delivery. Maternal and neonatal outcomes were also compared between groups. Multivariable linear regressions were used to assess time differences between groups, adjusting for known maternal and pregnancy characteristics.Results Compared with admitted patients, women managed expectantly at home had significantly longer PROM to delivery intervals (median 29.2 vs. 17 hours, p < 0.001), but were more likely to deliver within 24 hours of admission (95.1 vs. 82.9%, p = 0.004). In the adjusted analysis, PROM to delivery was 7 hours longer (95% confidence interval [CI]: 3.9–10.0) and admission to delivery was 5.3 hours shorter (95% CI: 2.8–7.7) in the outpatient expectant management cohort. There were no differences in secondary outcomes.Conclusion Outpatient management of term PROM is associated with longer PROM to delivery intervals, but shorter admission to delivery intervals.
Keywords: prelabor rupture of membranes; induction of labor; outpatient expectant management